Xerostomia among elderly patients – systematic review - Drożak, Martyna; Drożak, Paulina; Dziekońska, Justyna; Nowińska, Martyna; Grabowy, Paulina (Journal of Education, Health and Sport, 2021)
Introduction and purpose: Xerostomia is a salivary secretion malfunction that affects from 1 to 29% of the population. It is a common problem among elderly patients, however undeniably it still remains an underdiagnosed issue. Searching among available literature in the PubMed database with the following phrases: xerostomia; elderly, the aim of this article was to provide a broad review on the underdiagnosed problem which is xerostomia among elderly patients. Description: A group at risk of developing xerostomia are people over 65 years old and women in the perimenopausal period. Although dry mouth varies in etiology, geriatric patients mostly develop xerostomia as a result of head and neck radiotherapy, Sjögren syndrome or medication treatment. Untreated symptoms can lead to severe issues which heavily impact not only oral health of the patient, but also their everyday life quality, since xerostomia may lead into difficulty of speaking, swallowing and tasting. The plan of treatment is influenced by the etiology of the case, however it is aimed to stimulate salivary flow and eradicate the use of unnecessary medication which may cause dry mouth. Prevention of dry mouth is based on maintenance of good oral hygiene. Conclusions: Diagnosing the problem early can prevent patients from suffering the consequences of chronic xerostomia, therefore awareness should be brought to this issue. Dentist could also highly improve the quality of xerostomic patient’s life, if the chosen treatment significantly improved patient’s symptoms.